Regulating Working Hours in the Transition to Flexible Work - Olena Lutsenko; Anatolii P. Getman; Vladyslav S. Tkachenko; Ehor S. Nazymko (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2024)
The COVID-19 pandemic has led to a global shift toward remote and hybrid work, significantly transforming traditional work models. This study examines how these changes have impacted the structure of working hours and analyzes the adjustments made to Ukrainian legislation to address the new realities. It also explores strategies for improving Ukraine’s legal framework to foster better work-life balance and employee productivity. The research employs a combination of methods: analysis to evaluate changes in work schedules, synthesis to integrate various elements, induction to draw general conclusions, deduction to apply theories in practice, and abstraction to highlight core traits. Additionally, the study uses generalization to form broader statements. Findings indicate that the global move to flexible work has posed challenges to conventional working time regulations, necessitating new policies that protect workers' rights while balancing flexibility and fairness. With the increasing prevalence of remote and flexible work arrangements, legislative reforms are essential to ensure equitable and fair working hours for all. The findings offer recommendations for reforming Ukraine’s labor laws, aligning them with global trends, and advancing education in labor law and social security disciplines.